2023
DOI: 10.4068/cmj.2023.59.2.128
|View full text |Cite
|
Sign up to set email alerts
|

Urban-Rural Differences in the Prevalence of Depressive Symptoms in Korean Adults

Abstract: This study aimed to investigate the prevalence of depression among Koreans living in urban and rural areas, stratified by socioeconomic status. The study included 216,765 participants from the 2017 Korean Community Health Survey. Depressive symptoms were assessed using the PHQ-9, with a score of 10 or higher indicating depressive symptoms. Residences with the words Eup and Myeon in their addresses were categorized as rural areas, and residences with Dong in their addresses as urban areas. Socioeconomic status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…However, the relationship between residence and depressive symptoms is inconclusive in international epidemiology. For instance, a national study conducted in Korea reported that the prevalence of depressive symptoms was 1.29 times greater in urban settings than in rural ones [30]. Similar findings have been observed in Nordic regions, where among older adults, residing in urban areas is associated with higher odds of suffering from psychological distress [31,32].…”
Section: Discussionmentioning
confidence: 56%
“…However, the relationship between residence and depressive symptoms is inconclusive in international epidemiology. For instance, a national study conducted in Korea reported that the prevalence of depressive symptoms was 1.29 times greater in urban settings than in rural ones [30]. Similar findings have been observed in Nordic regions, where among older adults, residing in urban areas is associated with higher odds of suffering from psychological distress [31,32].…”
Section: Discussionmentioning
confidence: 56%
“…Differences in depressive symptoms among individuals from urban and rural areas have been an interesting research topic. Previous studies investigating the prevalence of depressive symptoms in urban and rural areas have reported inconsistent results ( 15 , 28 , 45 ). China Family Panel Studies examined 8,025, 7,808, and 4,887 older adults aged 60 years and above in 2016,2018, and 2020 and found that rural residents had a higher prevalence of depressive symptoms than urban residents ( 46 ).…”
Section: Discussionmentioning
confidence: 93%
“…Purtle et al ( 48 ) attributed the regional differences in depressive symptoms to urbanization, wherein urbanization increased the risk of mental health problems. Several studies have reported that urbanization is associated with the prevalence of depressive symptoms ( 45 , 49 ). Urban residents are more likely to have lower social support ( 49 ), and be exposed to stressors related to urban environments, including artificial light at night, neighborhood crime, traffic congestion, and noise ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations